Relationship of conflict resolution culture and personal characteristics of future doctors - O. I. Shcherbakova; K. G. Serdakova; A. V. Sorin; M. G. Kiseleva; N. A. Krylova; A. O. Komissarenko (Образование и наука)
Introduction. The article is devoted to the study of the relationship between conflict resolution culture and the personal characteristics of future doctors. Aim. The present research aimed to examine the relationship between the conflict resolution culture of medical university graduates and the key personality traits that influence a doctor’s professional activities: trust and aggressiveness. Methodology and research methods. The testing method employed various psychological tools, including O. I. Shcherbakova’s methodology for assessing the level of conflict resolution culture in individuals, J. B. Rotter’s Interpersonal Trust Scale, and the Bass-Darkey test, a standardised questionnaire designed to measure aggressive and hostile reactions developed by A. Bass and A. Darkey. Descriptive statistics, correlation analysis, regression analysis, and factor analysis were utilised to process the data. The study sample consisted of 300 graduates from the medical faculty of Sechenov University, aged between 22 and 28 years. Results. Graduates exhibit an average level of conflict resolution culture (46.6), an average level of interpersonal trust (78.6), and elevated indices of hostility (52.73) and aggressiveness (53.09), along with a high level of resentment (59.58). Correlation analysis of the study data identified 14 statistically significant relationships between the components of conflict resolution culture and various forms of aggression; however, no statistically significant relationships were found with the level of interpersonal trust. The multiple regression model developed by the authors indicated that 22.8% of the high level of conflict resolution culture can be attributed to the low levels of physical aggression and suspicion. Practical significance. A significant contribution of this study is the identification of the relationship between conflict resolution culture and the personal characteristics of medical university graduates, such as trust and aggressiveness. This research lays the groundwork for developing programmes aimed at enhancing the professionally important personality traits of future doctors. It emphasises the prevention of aggressive behaviour, the cultivation of conflict resolution skills, and the promotion of effective communication with patients and colleagues, ultimately leading to an improvement in the quality of medical care.